Hydrogen Spillover Accelerates Electrocatalytic Semi-hydrogenation of Acetylene in Membrane Electrode Assembly Reactor - Lv, Xue-Hui; Huang, Huan; Cui, Li-Ting; Zhou, Zhi-You; Wu, Wenkun; Wang, Yu-Cheng; Sun, Shi-Gang (ACS applied materials & interfaces, 2024)
Electrocatalytic acetylene semi-hydrogenation (EASH) offers a promising and environmentally friendly pathway for the production of C2H4, a widely used petrochemical feedstock. While the economic feasibility of this route has been demonstrated in three-electrode systems, its viability in practical device remains unverified. In this study, we designed a highly efficient electrocatalyst based on a PdCu alloy system utilizing the hydrogen spillover mechanism. The catalyst achieved an operational current density of 600 mA cm−2 in a zero-gap membrane electrode assembly (MEA) reactor, with the C2H4 selectivity exceeding 85%. This data confirms the economic feasibility of EASH in real-world applications. Furthermore, through in situ Raman spectroscopy and theoretical calculations, we elucidated the catalytic mechanism involving interfacial hydrogen spillover. Our findings underscore the economic viability and potential of EASH as a greener and scalable approach for C2H4 production, thus advancing the field of electrocatalysis in sustainable chemical synthesis.